Caracterização da resposta mediada por células T de memoria durante a leishmaniose cutânea e mucocutânea causada por Leishmania brasiliensis - Martins, Regia Ferreira (2019)
Leishmaniasis is a chronic disease with different clinical forms, which depend on the parasite species and the host's immune response. Localized Cutaneous Leishamnasis (LCL) is the most common form found in the world. Due to the importance of T-cell-media